Standard statistical calculations - Moore, P. G.; Edwards, Derek Ernest (London Sir Issac Pitman & Sons Ltd., 1965)
This book provides information on correlation and regression, multiple and quadratic regression. Although some of the examples are based on numerical and statistical data analysis.
mf 24/01/2019
Loans
Keywords: Statistics; London